Roles of IL-17A and IL-23 in the Pathogenesis of Ulcerative Colitis and Crohn’s Disease - Abdul-Hussein, Sarah S.; Ali, Ekhlass N.; Alkhalidi, Nawal M. F.; Zaki, Neihaya H.; Ad'hiah, Ali H. (Iraqi Journal of Science, 2021)
Inflammatory bowel disease (IBD) is a chronic inflammatory disorder, the etiology and pathogenesis of which have been suggested to be influenced by cytokines. Two main clinical types of IBD are recognized, namely ulcerative colitis (UC) and Crohn's disease (CD). The present study examined serum levels of two cytokines (IL-17A and IL-23) in 60 IBD patients (30 UC and 30 CD) and 30 healthy controls. The levels were correlated with age, gender, cigarette-smoking status, disease duration, family history, disease extension, symptoms, extra-intestinal manifestations, and medication. The results depicted that IL-17A level was significantly higher in UC and CD patients compared to control (45.2 ± 23.3 and 47.5 ± 34.4 vs. 15.6 ± 7.5 pg/ml, respectively; p < 0.001). Serum level of IL-23 was similarly increased in UC and CD patients compared to control (64.1± 23.7 and 62.5 ± 27.3 vs. 25.2 ± 11.1 pg/ml, respectively). However, the level of both cytokines showed no significant variation between UC and CD patients (p = 0.713 and 0.777, respectively). Distributing UC and CD patients into subgroups according to some characteristics revealed that IL-17A level was significantly increased in UC male compared to female patients (57.3 ± 18.2 vs. 34.5 ± 22.5 pg/ml; p = 0.005). It was also significantly increased in smoker UC patients compared with non-smoker patients (51.9 ± 19.4 vs. 31.6 ± 25.5 pg/ml; p = 0.022). Smoker CD patients also showed a significantly increased level of IL-23 compared to non-smoker patients (72.7 ± 28.5 vs. 52.2 ± 22.6 pg/ml; p = 0.038). In the case of family history, IL-23 level was significantly decreased in UC patients with a family history of IBD compared to CD patients with a family history (84.5 ± 24.3 vs. 50.4 ± 17.0 pg/ml.; p = 0.042). In conclusion, the present data suggest a role for IL-17A and IL-23 in the etiology and pathogenesis of UC and CD.